The concept of "Ilmu' Pagkausug" in the Jawi materials from Sulu - Hairulla, Munap H.
"Ilmu' pagkausug, one of the living traditions of Sulu which has certainly played a vital role in the development of the Tausug society and culture is largely remained unexplored and unstudied. Ilmu pagkausug, which consists in spiritual knowledge as understood by the Tausug mukali seekers, serves interesting purposes. For example, it may protect the one who possesses it against bad spirits and fellow humans who may wish to harm them. The one who has that ilmu pagkausug is called "pagkausugan," which explicitly means a powerful, invincible and learned person. This ilmu' pagkausug is transmitted, practiced, possessed and preserved by the Tausug Mukali seekers in the Jawi written tradition of Sulu. Specifically, ilmuh pagkausug has the following aspects: 1) ilmu (the sacred words), 2) ma-ana sin ilmu iban dagbus sin ilmu (the meaning or description and understanding), 3) ammal (application of the ilmu or knowledge), 4) pag-usal sin ilmu (technique or secrets of the ilmu), and 5) the duwaa ilmu (prayer or spells asking the Divine power to intervene).